2022
DOI: 10.1177/10892680221142020
|View full text |Cite
|
Sign up to set email alerts
|

The Hormesis Model for Building Resilience Through Adversity: Attention to Mechanism in Developmental Context

Abstract: In developmental science, resilience refers to children and youths’ ability to recover and pursue positive development in the face of stress related to adversity. Extant research has documented protective factors and ecological contexts that mitigate the impact of adversity and thereby promote resilience. One intriguing aspect of resilience is that individuals also develop strength in response to early adversity. However, very little theoretical guidance exists on the developmental mechanisms and contexts thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 122 publications
1
10
0
Order By: Relevance
“…The Yerkes–Dodson law (1908) and Hormesis Hypothesis (Oshri, 2022) suggest that stress is only beneficial for performance (i.e., eustress) until a threshold is reached and after which performance declines (i.e., distress). Our within-person results somewhat mirror these quadratic inverted U-shaped associations between stress and performance when partner support is included.…”
Section: Discussionmentioning
confidence: 99%
“…The Yerkes–Dodson law (1908) and Hormesis Hypothesis (Oshri, 2022) suggest that stress is only beneficial for performance (i.e., eustress) until a threshold is reached and after which performance declines (i.e., distress). Our within-person results somewhat mirror these quadratic inverted U-shaped associations between stress and performance when partner support is included.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, chronic, high levels of stress can be toxic, potentially damaging mental, emotional, and physical functioning. 18 Building resilience as a protective coping strategy may also help dampen susceptibility to occupational stress and burnout altogether. If one's resilience is strong, level of functioning under pressure has been shown to improve.…”
Section: Stress and Resiliencementioning
confidence: 99%
“…Studies have shown that low to moderate levels of stress may foster learning experiences and personal growth that improve resilience building and brain functioning while reducing mental illness risk. Conversely, chronic, high levels of stress can be toxic, potentially damaging mental, emotional, and physical functioning 18. Building resilience as a protective coping strategy may also help dampen susceptibility to occupational stress and burnout altogether.…”
Section: Stress and Resiliencementioning
confidence: 99%
“…While stress is perceived as a negative event, increasingly nuanced investigations of perceived stress and performance suggest a u-shaped association, with low-moderate levels of stress enhancing cognitive and physical performance, and high levels of stress, or no stress, diminishing performance. This emerging theory of stress, initially described by Rutter (2012) as a steeling effect, and more recently expressed as hormesis, a concept borrowed from the field of toxicology (Oshri et al, 2022; Oshri, 2022), is providing a more contextualized understanding of the interactions between individuals and their environments, suggesting that even external stressors can benefit human development when delivered in manageable amounts.…”
Section: The Problem For Researchers When Resilience Depends On Multi...mentioning
confidence: 99%